Public finance and right-wing populism - Linuz Aggeborn; Lovisa Persson (Research Institute of Industrial Economics (IFN), 2017)
We build a public finance model that explains why voters vote for right-wing populists, and also under which conditions established politicians will adopt a right-wing populist policy platform. Voters with lower private income have a stronger demand for basic public services at the expense of spending on a global good; generosity of refugee support systems, foreign aid, and environmental protection. Low income voters are thus more prone to support right-wing populists who oppose spending on such global goods. We conclude that established politicians that are challenged by right-wing populists will implement a policy with no global good spending if the relative cost of the global good is high enough. Additionally, adoption of right-wing populist policy is more likely when the economy is in a recession.
Keywords: D72; H39; D70; 330; Right-wing populism; Agency; Immigration